Meningkatkan Pemahaman Peserta Didik dalam Pembelajaran PAI Melalui Metode Jigsaw di Kelas X SMK Bina Patriot - Lestari, Hasri; Nisa, Khoerun; Rianijar Sukarman , Muhammad Reihan; Farida, Nur Aini; M. Makbul , M. Makbul (Najah Bestari, 2024)
This research aims to determine the increase in students understanding through the Jigsaw method in Islamic Religious Education (PAI) lessons in class X Bina Patriot Karang Bahagia Vocational School. The research method used in this research was descriptive qualitative and quantitative taken from 29 class X students at the planning, implementation, and evaluation stages. After the autor conducted interviews with class by providing a Jigsaw learning model, students can develop attitudes of mutual respect and cooperation between friends, provide space for students to discuss the material being studied, and encourage courage and show independence. Therefore, the Jigsaw learning strategy that PAI teachers can use when explaining and studying PAI lessons.